Advanced strategies to improve nitrification process in sequencing batch reactors - A review. (15th July 2018) - Jaramillo, Francisco; Orchard, Marcos; Muñoz, Carlos; Zamorano, Mauricio; Antileo, Christian
Abstract: The optimization of biological nitrogen removal (BNR) in sequencing batch reactors has become the aim of researchers worldwide in order to increase efficiency and reduce energy and operating costs. This research has focused on the nitrification phase as the limiting reaction rate of BNR. This paper analyzes different strategies and discusses different tools such as: factors for achieving partial nitrification, real-time control and monitoring for detecting characteristic patterns of nitrification/denitrification as end-points, use of modeling based on activated sludge models, and the use of data-driven modeling for estimating variables that cannot be easily measured experimentally or online. The discussion of this paper highlight the properties and scope of each of these strategies, as well as their advantages and disadvantages, which can be integrated into future works using these strategies according to legal and economic restrictions for a more stable and efficient BNR process in the long-term. Highlights: Relevant studies to improve nitrification in sequencing batch reactors are reviewed. Partial nitrification and bending point detection are examples of such strategies. Activated sludge models offer a quantitative evaluation of the biological reaction. Data-driven modeling is used for online estimation of critical process variables. Future research should focus on adequately integrating the reviewed strategies.